Problematic of Non Performing Banking Loans in Iraq and the Methods of Treatment - عبد الجبار, عبد الجبار هاني; سعيد, عفراء هادي (Journal of Economics and Administrative Sciences, 2016)
The banking system considered as one of the most important intermediate circle between creditor and debtors it is mean the most important funding rings in economic activity, whether finance takes the a consumer or investment form and therefore it is the main base to stimulate economic activity both on the demand side, both consumption and investment and therefore of the main motivating factors for economic growth.The banking system depends in achieve its goals on the grants and loan recovery, or what is known credit process and according to what the importance referred to the role of the banking system, it is important to ensure the safety and efficiency of the mechanisms of banking device and safety is the most important indicators safety work of the banking system, low non-performing bank loans size what we deal with in this research It sheds light on the concept of non-performing loans of various aspects of economic, administrative and legal and the reasons for this problem and its dimensions and implications and methods of treatment depending troubled banking system for the  Iraq beyond 2003 as a model for problem loans, their causes and effects and proposed actions for treatment.Finally, it must be noted that the global economic crisis, including the recent financial crisis in 2008 has shown the importance and need for the safety of the banking system work and the confidence of people.